Myocardial Infarction in a Premenopausal Woman on Leuprolide Therapy. (23rd June 2015) - Perez, Irving E.; Menegus, Mark A.; Taub, Cynthia C.
Abstract : Premenopausal women with chest pain syndrome may have nonatherosclerotic coronary arteries with abnormal coronary flow. Estrogens have cardioprotective effect improving coronary vasodilatation. This case report discusses the consequences of leuprolide use by decreasing estrogen levels which led to acute myocardial infarction.